2002
DOI: 10.1002/acp.784
|View full text |Cite
|
Sign up to set email alerts
|

Repeated interrogations: verbal and non‐verbal cues to deception

Abstract: The major aim of this study was to investigate to what extent verbal and non-verbal features of liars' and truth-tellers' behaviour change during the course of repeated interrogations. After seeing a staged event, 24 suspects (12 liars and 12 truth-tellers) were interrogated three times over a period of 11 days. In terms of the non-verbal features, and in line with our prediction, we found that the liars displayed significantly fewer smiles, self-manipulations, pauses, and less gaze aversion than truthtellers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 14 publications
(12 reference statements)
7
114
2
Order By: Relevance
“…Given the importance, it is surprising that truth tellers' and liars' strategies to appear credible in an interview have been understudied for a long time (DePaulo, Lindsay, Malone, Muhlenbruck, Charlton, & Cooper, 2003). However, DePaulo et al's (2003) plea for research into this area has resulted in several studies (Colwell, Hiscock-Anisman, Memon, Woods, & Michlik, 2006;Granhag & Strömwall, 2002;Strömwall, Granhag, & Landström, 2007;Strömwall, Hartwig, & Granhag, 2006). …”
mentioning
confidence: 99%
“…Given the importance, it is surprising that truth tellers' and liars' strategies to appear credible in an interview have been understudied for a long time (DePaulo, Lindsay, Malone, Muhlenbruck, Charlton, & Cooper, 2003). However, DePaulo et al's (2003) plea for research into this area has resulted in several studies (Colwell, Hiscock-Anisman, Memon, Woods, & Michlik, 2006;Granhag & Strömwall, 2002;Strömwall, Granhag, & Landström, 2007;Strömwall, Hartwig, & Granhag, 2006). …”
mentioning
confidence: 99%
“…Particularly relevant to arousal-based interview protocols is the belief that liars exhibit increased gaze aversion and body movements. Research has not only failed to support these beliefs, but there is evidence of the opposite effect (Granhag & Stromwall, 2002). These reviews of the deception detection literature confirm that the current arousal-based methods utilized by the law enforcement community may not be the most effective means by which to identify deceit (DePaulo et al, 2003;Vrij, 2008;Vrij, Mann, & Fisher, 2006a).…”
Section: Literature Review Arousal Based Protocolsmentioning
confidence: 80%
“…In numerous studies, participants have reported that telling a lie is more cognitive demanding than telling the truth (Granhag & Stromwall, 2002;Stromwall, Hartwig, & Granhag, 2006;Vrij, Edward & Bull;2001;Vrij et al, 2006b;Vrij et al, 1996). These reports support the notion that lying requires more cognitive resources than truth-telling and that individuals are aware of increased cognitive demands that accompany deception.…”
Section: Deception and Cognitive Loadmentioning
confidence: 83%
“…Preparation enables liars to avoid the need to improvise spontaneous lies (Vrij, Granhag, Mann, & Leal, 2011) and to stick to their cover story during the interview and hence provide a consistent statement (Granhag & Strömwall, 2002;Vrij et al, 2009). …”
Section: Counter-interrogation Strategies In Lie Detection Contextsmentioning
confidence: 99%
“…Their primary focus is to provide detailed and consistent statements rather than statements similar to those of truth-tellers (Deeb, Vrij, Hope, Mann, Granhag, & Lancaster, 2017;Harvey, Vrij, Leal, Hope, & Mann, 2017;Sakrisvold, Granhag, & Mac Giolla, 2017;Strömwall & Willén, 2011). Although they are able to provide statements that resemble those of truth-tellers if they are equally familiar with the reported event (Blandón-Gitlin et al, 2005;Warmelink et al, 2013), their concern about being detailed and consistent may make them more detailed and consistent than truth-tellers when they employ counter-interrogation strategies (Deeb, Vrij, Hope, Mann, Granhag, & Lancaster, 2017;Granhag & Strömwall, 2002;Harvey, Vrij, Leal, Hope, et al, 2017). In other words, liars who are familiar with the reported event or interview technique may not necessarily provide statements similar to those of truth-tellers.…”
Section: The Self-regulation Theorymentioning
confidence: 99%